(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Musa paradisiaca L. is native to tropical climate. Inflorescences of this herb are used as a treatment of digestive distresses. This study involved analysis of the fatty acid contents and some in-vitro pharmacological activities of the inflorescence. Modified Kupchan method was used for extraction in solvents of varying polarity. Fatty acid content analysis was conducted on n-hexane extract; Palmitoleic acid was found to be the highest in proportion in both bound (34.40%) and free (37.80%) forms. n-hexane and dichloromethane extracts exhibited cytotoxicity against carcinoma cell (HeLa cell line). Ethyl acetate extract possessed significant amount of free radical (DPPH) scavenging capability (IC50 = 66.92±0.3065 μg/ml). The n-Hexane extract was found to be rich in phenolics (26.40 ± 0.033 mg GE/g) and flavonoids (83.40± 0.099 mg QE/g). Dichloromethane fraction exhibited the highest zone of inhibition (15 mm) against the bacterium Shigella dysenteriae. Ethyl acetate fraction showed blood clot lysis activity of 29.35% (standard streptokinase 63.05%). Presence of potent bioactivities imply the prospects of this sample as a source of lead compounds for effective formulations against chronic digestive diseases. Dhaka Univ. J. Pharm. Sci. 23(1): 69-76, 2024 (June)